2020
DOI: 10.5194/gmd-2020-191
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recalibrating Decadal Climate Predictions – What is an adequate model for the drift?

Abstract: Abstract. Near-term climate predictions such as decadal climate forecasts are increasingly being used to guide adaptation measures. To ensure the applicability of these probabilistic predictions, inherent systematic errors of the prediction system must be corrected. In this context, decadal climate predictions have further characteristic features, such as the long time horizon, the lead-time dependent systematic errors (drift) and the errors in the representation of long-term changes and variability. These fea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, this is just one of many possible options that could be considered. A more efficient strategy for model selection based on boosting [36] is currently under investigation for this use case.…”
Section: Model Selectionmentioning
confidence: 99%
“…However, this is just one of many possible options that could be considered. A more efficient strategy for model selection based on boosting [36] is currently under investigation for this use case.…”
Section: Model Selectionmentioning
confidence: 99%
“…Meanwhile, improvements in trends effectively adjusted the long-term climate behavior in forecasts to match observations (Kharin et al, 2012). To correct errors associated with the representation of temporal changes and variability, Pasternack et al (2020) adopted a time-varying mean to characterize the climate trend in the calibration of decadal temperature forecasts. In addition to these decadal-scale calibrations, recent studies suggested that seasonal climate forecasting could also benefit from correcting time-dependent errors.…”
Section: Introductionmentioning
confidence: 99%